The creativity of farmers participating in contract farming to drive the economic activities of rural area - Rustinsyah, Rustinsyah; Prasetyo, Djoko Adi; Handayani, Pinto Rukmi (Masyarakat, Kebudayaan dan Politik, 2025)
This study elaborates on the creativity of melon farmers to overcome problems and gain benefits in this inherently high-risk farming. The research was conducted in the villages of Plumpang District, an area in East Java known for its quality melon produce. Data were collected from 100 respondents from these villages. Respondents were selected purposively by considering demographic and farming characteristics. The relationship between contract farming and farmer creativity was examined using Spearman Rank analysis. Statistical test confirms the relationship between contract farming practices and melon farmers’ creativity. The low correlation is due to the determining factor, namely, extreme climatic conditions, which have a damaging impact on crops. Furthermore, an increase in investment ranks first among the nine indicators of farmer creativity. This implies that contract farming practice is highly correlated with increased investment. Moreover, the majority (75%) of farmers’ profit from contract farming increases investment. This study concludes that these creative farmers empowered by contract farming promote economic activity in rural areas. These findings will be useful as a starting point for future research on the effects of contract farming as a driver of economic activity and its subsequent contribution to the sustainability of rural development.